STRATEGI PENGEMBANGAN PARIWISATA RAMAH MUSLIM DI PANTAI KUTA, NUSA TENGGARA BARAT: (STRATEGY FOR DEVELOPING MUSLIM-FRIENDLY TOURISM IN KUTA BECH, WEST NUSA TENGGARA) - Hakim, Arif Luqman; Rifa'i, Mochamad Novi (UPT Penerbitan Universitas Jember, 2024)
Muslim-friendly tourism is relatively new in the world of tourism. In the tourism industry there are many aspects and actors that contribute, the aspects and actors in it must be in line with sharia and not contrary to religious standards, the standardization meets halal and good criteria. One of the areas that promotes the Muslim-friendly tourism sector is West Nusa Tenggara province and one of the Special Economic Zones (SEZs) is Kuta beach. This study aims to analyze the development strategy of Muslim-friendly tourism on the coast of Kuta, Central Lombok, West Nusa Tenggara. The method in this study is qualitative using case studies. The results of this study show that the NTB Provincial Government through the NTB Tourism Office and Central Lombok Regency provide full support by making human development training, regulations, and laws on Muslim-friendly tourism.